Cloud Scheduling using Meta Heuristic Algorithms - Jain, A; Upadhyay, A (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing has transformed into a well-known in area of high performance, cloud computing as it offers on-request access to shared pool of resources over web in a self-service, dynamically scalable. One of the important research issues which need to be focused for its efficient performance on task scheduling which plays the key role for increase the efficiency of whole cloud computing facilities. implies that to assign best suitable resources for the requested task to be execute with the various parameters like time, cost, scalability, makespan, reliability, resource utilization, accessibility, throughput etc. In this paper, we give survey and relative studies of a few task scheduling using metaheuristic algorithms for cloud computing.